1993
DOI: 10.1002/pen.760331510
|View full text |Cite
|
Sign up to set email alerts
|

Rheological behavior and processability of neoprene and acrylic rubbers

Abstract: Rheological behavior of neoprene and acrylic rubbers and their carbon blackfilled compounds has been studied using a Monsanto Processability Tester. These systems show pseudoplastic flow behavior. Die swell increases with increase in shear rate up to a limit beyond which it decreases. It also decreases with increase in filler loading and temperature. The maximum recoverable deformation has been calculated by assuming that the viscous response of the rubbers obeys the power law model and elastic behavior is des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The increase in die swell with increasing shear rate may be attributed to the considerable increase in the recoverable elastic energy of the system at higher shear rates. The increase in temperature increases the mobility of the polymer chain, which reduces the capacity of polymer molecules to store the elastic energy and, hence, there is a reduction in the die swell values 20–22. Die swell at 6 wt % of EMA is maximum at any shear rate, implying that optimum compatibilization leads to a physically entangled structure of a three‐dimensional network, which obstructs the chains to move past one another.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in die swell with increasing shear rate may be attributed to the considerable increase in the recoverable elastic energy of the system at higher shear rates. The increase in temperature increases the mobility of the polymer chain, which reduces the capacity of polymer molecules to store the elastic energy and, hence, there is a reduction in the die swell values 20–22. Die swell at 6 wt % of EMA is maximum at any shear rate, implying that optimum compatibilization leads to a physically entangled structure of a three‐dimensional network, which obstructs the chains to move past one another.…”
Section: Resultsmentioning
confidence: 99%
“…In their earlier work, they also reported the processability of a neoprene and acrylate rubber blend 14 . Lipatov et al 15 reported the effect of fillers on the rheological characteristics of polyvinyl acetate and ethylene vinyl acetate, using a cone -plate rheometer.…”
Section: Introductionmentioning
confidence: 99%